2019
DOI: 10.3892/ijmm.2019.4376
|View full text |Cite
|
Sign up to set email alerts
|

Osteoadherin serves roles in the regulation of apoptosis and growth in MC3T3‑E1 osteoblast cells

Abstract: Small leucine-rich proteoglycans (SLRPs) are a class of proteoglycans that are characterized by small protein cores and structures of leucine-rich repeats. SLRPs are expressed in most extracellular matrices and share numerous biological functions that are associated with binding of collagens and cell surface receptors. Osteoadherin (also termed osteomodulin) is encoded by the Omd gene and is a keratan sulfate proteoglycan of the class II subfamily of SLRPs. Osteoadherin is highly expressed in mineralized tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This idea is supported by our observation of increased osteoblast calcium deposition in response to the highest tested concentrations of rOMD. OMD is known to reduce apoptosis in osteoblasts (28), thus supporting a role for OMD in promoting new bone formation and cell survival. Indeed, in our patient cohort upregulated OMD expression correlates with upregulation of serine 118 phosphorylation on pro-apoptotic protein BCL2-associated agonist of cell death (BAD).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This idea is supported by our observation of increased osteoblast calcium deposition in response to the highest tested concentrations of rOMD. OMD is known to reduce apoptosis in osteoblasts (28), thus supporting a role for OMD in promoting new bone formation and cell survival. Indeed, in our patient cohort upregulated OMD expression correlates with upregulation of serine 118 phosphorylation on pro-apoptotic protein BCL2-associated agonist of cell death (BAD).…”
Section: Discussionmentioning
confidence: 98%
“…4B). As OMD has previously been associated with resistance to apoptosis (28), we also tested whether OMD expression affected anoikis resistance and stemness of breast cancer cells through mammosphere formation and mammosphere self-renewal assays. OMD expression showed no significant effect on mammosphere formation or self-renewal (Supplemental Fig.…”
Section: Omd Increases Breast Cancer Cell Migration In Vitro and Bone...mentioning
confidence: 99%
“…Hodgkinson found Abi3bp-knockout increased BMSC proliferation but limited their motility and ability of osteogenic and adipogenic differentiation, indicating that Abi3bp played a role in switching BMSCs between proliferative and differentiating states 28 . Omd (osteomodulin, also known as osteoadherin; OSAD; SLRR2C) encodes a keratan sulfate proteoglycan and usually highly expressed in mineralized tissues 29 . The protein binds to BMP2 via its terminal leucine-rich repeats and thus promotes BMP/SMAD signal activation, osteogenesis-associated gene transcription and mineralized nodule formation 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more and more studies have found that SLRPs were involved in regulating multiple signaling pathways that control cell proliferation, differentiation, immunity, inflammation, metabolism, and so on 6,9,17,22,24,32 . Previous studies have suggested that possible mechanisms of action include: (a) structural proteins of ECM, which can maintain the stability of the matrix by affecting signal transduction pathways; (b) mainly located outside the cell, where they are located in multiple signal cascades upstream, it forms a signal‐regulating network and affects intracellular phosphorylation; and (c) interacts with extracellular receptors (such as tyrosine kinase receptors and toll‐like receptors) to initiate downstream signaling pathways.…”
Section: Structure and Characteristics Of Slrpsmentioning
confidence: 99%
“…Further research found that decorin and podocan are involved in the development of diabetic nephropathy 10,19 . In addition, some studies have found that SLRPs (decorin, biglycan, lumican, TSK, osteoadherin, osteoglycin, asporin) are shown to be involved in the pathogenesis of tumors by modulating the proliferation, apoptosis, invasion, and migration of the cancer cells 8,20–24 …”
Section: Introductionmentioning
confidence: 99%